Smooth muscle cell hypertrophy versus hyperplasia in hypertension. - Owens, G K (1981)
Arteries of hypertensive animals have a greater mass of smooth muscle than those of normotensive controls. We examined the contribution of smooth muscle cell hypertrophy and hyperplasia to this increase in mass. Cell size measurements obtained by (i) image analysis of enzyme-dispersed cells, (ii) morphometric evaluation of tissue sections, and (iii) biochemical measures of protein/cell and actin/cell ratios on isolated cells showed that average cell size was greater in spontaneously hypertensive rats than in normotensive Wistar-Kyoto and Sprague-Dawley controls. Average DNA/cell ratios were also increased in spontaneously hypertensive rats while protein/DNA ratios were not different. Analysis of nuclear DNA content of individual cells by flow microfluorimetry and Feulgen-DNA microdensitometry measurements showed that greater than 20% of spontaneously hypertensive rats cells were polyploid while less than 10% of control cells were polyploid. Estimates of cell number per centimeter of aortic length, based on ploidy and DNA content, show no difference between control and hypertensive rats. Thus, smooth muscle hypertrophy alone accounts for the increased mass of smooth muscle in aortas of spontaneously hypertensive rats. Furthermore, this cellular hypertrophy is accompanied by a change in nuclear ploidy. This nuclear response in hypertension may represent a fixed change related to the establishment of a chronic hypertensive state.